1993
DOI: 10.1063/1.465822
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational modulation effects on the hyperfine coupling constants of fluoromethyl radicals

Abstract: A general quantum-mechanical protocol for the study of nonrigid free radicals has been applied to the series CH 3 , CH 2 F, CHF 2 , and CF 3 . Electronic structures have been computed by highly correlated ab initio methods and vibrational modulation effects have been studied by a nonrigid invertor Hamiltonian. The effect of small amplitude vibrations perpendicular to the inversion motion has been taken into account by an adiabatic model. The results are in close agreement with experiment, and can be interprete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 64 publications
7
48
0
Order By: Relevance
“…The calculated inversion barrier was 50.1 cm Ϫ1 and the energy minimum occurred at ϭ 22.3°. These numbers are in satisfying agreement with the results of Barone et al 10 Their QCISD(T) results with the 6-311G** basis set gave (interpolating the results from their Table 7): R NH ϭ 1.015 Å, R NO ϭ 1.263 Å, and HNH ϭ 117.6°for C s (E ϭ Ϫ130.855301), and R NH ϭ 1.0128 Å, R NO ϭ 1.262 Å, and HNH ϭ 119.43°(E ϭ Ϫ130.85507) for C 2v . The minimum was at ϭ 22.0°and the inversion barrier was 51.3 cm Ϫ1 .…”
Section: H 2 Nosupporting
confidence: 94%
See 2 more Smart Citations
“…The calculated inversion barrier was 50.1 cm Ϫ1 and the energy minimum occurred at ϭ 22.3°. These numbers are in satisfying agreement with the results of Barone et al 10 Their QCISD(T) results with the 6-311G** basis set gave (interpolating the results from their Table 7): R NH ϭ 1.015 Å, R NO ϭ 1.263 Å, and HNH ϭ 117.6°for C s (E ϭ Ϫ130.855301), and R NH ϭ 1.0128 Å, R NO ϭ 1.262 Å, and HNH ϭ 119.43°(E ϭ Ϫ130.85507) for C 2v . The minimum was at ϭ 22.0°and the inversion barrier was 51.3 cm Ϫ1 .…”
Section: H 2 Nosupporting
confidence: 94%
“…This adiabatic approximation has been used in particular by Barone et al 10 in a study of H 2 NO [with ⌬V(s) neglected], to which we will refer later.…”
Section: General Approachmentioning
confidence: 97%
See 1 more Smart Citation
“…34 We have previously shown that the effect of this motion can be effectively evaluated using the distinguished coordinate ͑DC͒ approach, 61,62 in which all the geometrical parameters are optimized at selected value of the out-ofplane displacement of the H ␣ atom. 12,63 The energy profile corresponding to this displacement has been computed by the 6-31ϩG(d,p) basis set, which provides an harmonic frequency of 558 cm Ϫ1 and an anharmonicity constant of 15 cm Ϫ1 . The energy profile and the corresponding vibrational levels are sketched in Fig.…”
Section: A Fermi Contact Termsmentioning
confidence: 99%
“…Full line ® variational results, dashed line ® EN perturbation results, dotted line ® MPB perturbation results. Horizontal full line ®``experimental'' value (28 Gauss[16], see text) The same asFig. 3but with the aimed + property selection procedure.…”
mentioning
confidence: 99%